Antinociceptive Effects of Lipid Raft Disruptors, a Novel Carboxamido-Steroid and Methyl β-Cyclodextrin, in Mice by Inhibiting Transient Receptor Potential Vanilloid 1 and Ankyrin 1 Channel Activation - Horváth, Ádám; Biró-Sütő, Tünde; Kántás, Boglárka; Payrits, Maja; Skoda-Földes, Rita; Szánti-Pintér, Eszter; Helyes, Zsuzsanna; Szőke, Éva (Frontiers in Physiology, 2020)
Transient Receptor Potential Vanilloid 1 and Ankyrin 1 (TRPV1, TRPA1) cation channels are expressed in nociceptive primary sensory neurons, and play an integrative role in pain processing and inflammatory functions. Lipid rafts are liquid-ordered plasma membrane microdomains rich in cholesterol, sphingomyelin and gangliosides. We earlier proved that lipid raft desintegration by cholesterol depletion using a novel carboxamido-steroid compound (C1) and methyl β-cyclodextrin (MCD) significantly and concentration-dependently inhibit TRPV1 and TRPA1 activation in primary sensory neurons and receptor-expressing cell lines. Here we investigated the effects of C1compared to MCD in mouse pain models of different mechanisms. Both C1 and MCD significantly decreased the number of the TRPV1 activation (capsaicin)-induced nocifensive eye-wiping movements in the first hour by 45% and 32%, respectively, and C1 also in the second hour by 26%. Furthermore, C1 significantly decreased the TRPV1 stimulation (resiniferatoxin)-evoked mechanical hyperalgesia involving central sensitization processes, while its inhibitory effect on thermal allodynia was not statistically significant. In contrast, MCD did not affect these resiniferatoxin-evoked nocifensive responses. Both C1 and MCD had inhibitory action on TRPA1 activation (formalin)-induced acute nocifensive reactions (paw liftings, lickings, holdings and shakings) in the second, neurogenic inflammatory phase by 36% and 51%, respectively. These are the first in vivo data showing that our novel carboxamido steroid compound exerts antinociceptive and antihyperalgesic effects by lipid raft disruption surrounding the TRPV1 and TRPA1 ion channels similarly to MCD, but in 150-fold lower concentrations. It is concluded that C1 is a useful experimental tool to investigate the effects of cholesterol depletion in animal models, and it also might open novel analgesic drug developmental perspectives.